Salicylic acid alleviated the effect of drought stress on photosynthetic characteristics and leaf protein pattern in winter wheat - Masoumeh Khalvandi; Adel Siosemardeh; Ebrahim Roohi; Sara Keramati (Heliyon, 2021)
Salicylic acid (SA) is a promising compound to increase plant tolerance to drought stress, and it can affect many aspects of physiological and biochemical processes. This study was focused on the changes in proteins, photosynthesis, and antioxidant system of Sardari wheat ecotypes leave in response to the application of SA under drought stress conditions. Treatments included Sardari wheat ecotypes (Baharband, Kalati, Fetrezamin, Gavdareh, Telvar, and Tazehabad), salicylic acid at 0.5 mM (controls were untreated), and drought stress (30% of the field capacity). The results showed that membrane electrolyte leakage, and lipid peroxidation of all six ecotypes, were obviously increased under drought stress conditions. On the other hand, drought stress decreased leaf chlorophyll content, photosynthetic rate, stomatal conductance, carboxylation efficiency, and transpiration rate. The results of SDS-PAGE indicated that the abundance of some protein spots was downregulated when the plants were exposed to drought stress, while other protein spots’ abundance was upregulated in such a situation. Under stress conditions, the highest antioxidant enzymatic activity, photosynthetic performance, cell membrane stability, and numbers of protein bands were observed in Baharband and Telvar, while the lowest was related to Fetrezamin. Salicylic acid treatments effectively ameliorated the negative effects of drought stress on Sardari ecotypes through improving the photosynthetic performance, keeping membrane permeability, induction of stress proteins, and enhancing the activity of antioxidant enzymes. The above findings suggest that ecotype ability to maintain photosynthetic performance was important to cope with drought stress.